The changing face of multiple sclerosis: Prevalence and incidence in an aging population. (September 2015) - Solaro, C; Ponzio, M; Moran, E; Tanganelli, P; Pizio, R; Ribizzi, G; Venturi, S; Mancardi, GL; Battaglia, MA
Objective: To assess multiple sclerosis (MS) incidence from 1998 to 2007, and MS prevalence on 31 December 2007, in the province of Genoa, Italy. Methods: We identified MS cases diagnosed before 31 December 2007 by analyzing archives of hospitals with neurological or rehabilitation wards, the local Italian MS society, family doctor records and requests for oligoclonal band analysis on cerebrospinal fluid (CSF). Results: A total of 1312 MS patients were residing in the province of Genoa on the prevalence day; 431 (32.85%) were men and 881 (67.15%) were women; mean age was 50.6 (± 13.9). The overall crude MS prevalence rate was 148.5/100, 000; 103.1/100, 000 in men and 189.1/100, 000 in women. The crude mean annual MS incidence rate was 6.6 cases/100, 000 (4.4/100, 000 men; 8.6/100, 000 women). Mean age at diagnosis was 39.5 ± 12.3 (men: 39.9 ± 13.0; women: 39.3 ± 11.9). A mean annual incidence of 4 MS patients ≥ 60 was observed. Conclusions: We observed an increased MS prevalence in the province of Genoa, compared to 1997. The mean age at diagnosis was relatively high (39 years old), 18% of our MS patients were over 65, and a notable incidence increase was seen in patients over 60. This has important implications, in terms of the need to organize the health system to better serve elderly MS patients, especially considering comorbidities and different medical needs of elderly MS patients; and to increase awareness within the medical community about the increasing risk of newly-presenting MS in the older population.